2019
DOI: 10.1002/acr.23784
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Hand and Upper Arm Functional Disability in People With Rheumatoid Arthritis: A Systematic Review

Abstract: Objective. This original systematic review aimed to summarize evidence within observational studies on the factors associated with hand functional disability in adults with rheumatoid arthritis (RA).Methods. A rigorous extensive systematic literature search was conducted in 6 medical databases for peerreviewed English language observational studies that explore the factors associated with hand function for people with RA. Factors were critically classified under the domains of the International Classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It has been shown that functionality of the dominant hand is more affected when synovial inflammation is present, and so disease activity was identified as one of the most influential factors on hand function in RA patients. 21 Actually, when RA is within higher disease activity, many other joint parts are affected such as skeletal muscle, cartilage, ligaments and tendons; in this way, as well as synovitis, the worsening of these structures leads to a decrease in physical hand function. 22 In our sample, a relationship between hand function and disease activity was found, confirming these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that functionality of the dominant hand is more affected when synovial inflammation is present, and so disease activity was identified as one of the most influential factors on hand function in RA patients. 21 Actually, when RA is within higher disease activity, many other joint parts are affected such as skeletal muscle, cartilage, ligaments and tendons; in this way, as well as synovitis, the worsening of these structures leads to a decrease in physical hand function. 22 In our sample, a relationship between hand function and disease activity was found, confirming these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Dedeoglu and his colleagues [26] in their study determined that grip strength was significantly related to disability and impairment, disease activity, and articular damage. A systematic review of twenty articles by Arab Alkabeya and colleagues [27] found out that grip strength and disease activity were identified as the most influential factors on hand function in people with RA. Similar to this study, Taştekin et al [28] and Dedeoglu et al [26] reported that grip strength was negatively correlated with the DAS 28 whereas in patients with relatively early RA and relatively lesser deformities, hand strength is affected more by disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in previous critical appraisals using AXIS, a percent value was predetermined at the beginning of this study to identify publications as high or low quality (Arab Alkabeya et al, 2019; Boxberger and Reimers, 2019; Henderson et al, 2019). For this study’s critical appraisal, the authors predetermined the value of a high-quality publication as total appraisal scores equal to or exceeding 70% of the total (i.e., at least 14 out of 20 questions scored as 1, or a score ≥14 to compensate for some items where there was no consensus scored at 0.5).…”
Section: Methodsmentioning
confidence: 99%